Abstracts Radioprotection et Conférences JRANF 2025_JAIM 2025_17.3 - MOIFO Boniface; SONHAYE LANTAM; Abdoulaye DIONE DIOP; ADJADOHOUN Sonia B.M.G; AMADOU Abdoulatif; MOYIKOUA Régis Franck; GUI BILE Lynda; KONE Abdoulaye; ZOUZOU Ange Éric Ghislain; TCHAOU MAZAMAESSO; et al. (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2025)
2-Abstracts Radioprotection et Conférences JRANF 2025_JAIM 2025_17.3